THE DIVERSITY OF NON-TUBERCULOUS MYCOBACTERIA SPECIES IN OUR REGION. (International Journal of Food and Nutritional Sciences, 2022)
Opportunistic infections caused by non-tuberculous mycobacteria have been seen in both immunocompromised and immunocompetent hosts in recent years. The purpose of this research is to learn how common NTM species are in TB patients (both pulmonary and extrapulmonary) in a tertiary care hospital in Pondicherry, to compare several phenotypic and genotypic approaches to NTM identification, and to find out what patterns their DSTs show.